High efficiency single-pass SHG of low power CWML and QML laser in an MgO:PPLN. (October 2018) - He, Chaojian; Yu, Haijuan; Zhang, Jingyuan; Zou, Shuzhen; Zhang, Ling; Qi, Yaoyao; Li, Bei; Lin, Xuechun
Highlights: This study investigates a high repetition ps green laser based on MgO:PPLN. The conversion efficiency in the QML is higher than in the CWML. We achieved high efficiency green light based on a low power QML laser. The method can be extended to other frequency-doubling crystals. Abstract: We present the second harmonic generation (SHG) of a low power and of both Q-switched mode-locked (QML) and CW (CWML) mode-locked picosecond (ps) laser at 1064 nm based on a single-pass frequency-doubling configuration of an end-pumped passively mode-locked Nd:YVO4 laser in a 3-mm periodically poled MgO-doped lithium-niobate (MgO:PPLN). The maximum SHG conversion efficiency is 27.4% when the laser is operated in the QML mode at an averaged pumping power of 895 mW and the conversion efficiency is reduced to 24.1% in the CWML mode with a maximum averaged pumping power of 1.37 W. The corresponding pulse width of the SHG output is estimated to be 15.5 ps. The repetition rates of the laser are 137 kHz for QML and 78.7 MHz for CWML. The theoretical efficiencies of SHG are calculated in both QML and CWML and the results agree very well with the experiments especially in the QML. This work provides a useful method for efficient frequency conversion for low power mode-locked lasers.